The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.marchem.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Daily variability of dissolved inorganic radiocarbon at three sites in the surface ocean

Abstract: We report radiocarbon measurements of dissolved inorganic carbon (DIC) in surface water samples collected daily during cruises to the central North Pacific, the Sargasso Sea and the Southern Ocean. The ranges of Δ 14 C measurements for each cruise (11-30‰) were larger than the total uncertainty (7.8‰, 2-sigma) of the measurements. The variability is attributed to changes in the upper water mass that took place at each site over a two to four week period. These results indicate that variability of surface Δ 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Based on the uncertainty in bomb-14 C inventory (15%) and the integral of the atmosphere-ocean D 14 C gradient (5%), the uncertainty of 14 C-based exchange rates estimated to $20%. Druffel and Griffin [2008] showed that for surface samples, the total uncertainty of a DIC D 14 C value at a given site over a several week period is approximately two times the reported uncertainty ($7‰). Thus, depending on the application, post-bomb D 14 C data should consider this shortterm variability of surface ocean D 14 C values and factor this into their analysis as it might affect the estimates of air-sea CO 2 exchange rates.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on the uncertainty in bomb-14 C inventory (15%) and the integral of the atmosphere-ocean D 14 C gradient (5%), the uncertainty of 14 C-based exchange rates estimated to $20%. Druffel and Griffin [2008] showed that for surface samples, the total uncertainty of a DIC D 14 C value at a given site over a several week period is approximately two times the reported uncertainty ($7‰). Thus, depending on the application, post-bomb D 14 C data should consider this shortterm variability of surface ocean D 14 C values and factor this into their analysis as it might affect the estimates of air-sea CO 2 exchange rates.…”
Section: Resultsmentioning
confidence: 89%
“…Druffel and Griffin [2008] showed that for surface samples, the total uncertainty of a DIC D 14 C value at a given site over a several week period is approximately two times the reported uncertainty ($7‰). Thus, depending on the application, post-bomb D 14 C data should consider this shortterm variability of surface ocean D…”
mentioning
confidence: 89%
“…The cause(s) of the apparent temporal DOC (Druffel and Griffin 2008), approximately 100‰ higher than that in 2015. This means that DOC produced from sinking POC would have a ∆ 14 C value that was approximately 100‰ higher in the 1980s than that in 2015.…”
Section: Temporal Variabilitymentioning
confidence: 84%
“…upwelling. (Druffel and Griffin 2008): the north central Pacific (1985, 1987 and 1999, circles), and the Sargasso Sea (1989 and2000, squares) and the dashed line is the least-squares fit of these data. …”
Section: Resultsmentioning
confidence: 99%
“…Seawater samples were collected from 00.5 m depth using a plastic bucket as described previously (Druffel and Griffin 2008). Sea surface temperature (SST) measurements were made using an ethanol thermometer (±0.2 C).…”
Section: Methodsmentioning
confidence: 99%